Die Alpen im Spannungsfeld der europäischen Raumordnungspolitik: Anmerkungen zum EUREK-Entwurf auf dem Hintergrund des aktuellen Strukturwandels im Alpenraum - Bätzing, Werner (Raumforschung und Raumordnung | Spatial Research and Planning, 1999)
The first part of this article consists of a local-authority level analysis of the structural changes currently in process in the Alps Region, which are then categorised at regional level. In simple terms this process can be described as one of “urbanisation and depopulation”; however, the wide disparities which are evident do call for regionally specific strategies. Since transnational co-operation has been established for some ten years in the Alps with the Alpine Convention, and with the REGIONALP project initiated under EFRE Art. 10 being intended to enhance and to add concrete detail to the ESDP draft from below, the second part of this article is devoted to an examination and appraisal of the ESDP draft from the perspective of experiences gathered in the Alps. The fact that the Alpine Convention and ESDP have a good deal in common means that experience in the Alps could well provide valuable stimuli for the ESDP process.
Keywords: Article